PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN HOTEL RESTY MENARA PEKANBARU - Edlin, Roki Putra; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research seeks to investigate the impact of leadership and job satisfaction on turnover intention in Employees Resty Menara Hotel Pekanbaru. This research used 70 respondents as samples taken from a total sampling technique. This study adopts a quantitative descriptive research approach, utilizing primary data for analysis. The data analysis method in this research uses multiple regression analysis. The findings of this study reveal that there is a negative and significant influence between leadership on turnover intention. And job satisfaction also has a negative and significant effect on turnover intention. And leadership and job satisfaction together have a negative effect on turnover intention.The coefficient of determination test demonstrates an adjusted value of 43.1%, indicating that these variables collectively account for 43.1% of the variation in turnover intention in the value relevance approach. The remaining 56.9% is attributed to unexamined variables. Keywords : Kepemimpinan;Kepuasan Kerja;Turnover Intention